Thought Contributions of Paulo Freire and Abdurrahman Wahid in Educational Philosophy - Saefudin, Ahmad; Rokhmah, Hanny; Alhairi, Alhairi (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2022)
The purpose of this article is to identify the philosophical ideas of Paulo Freire and KH. Abdurrahman Wahid or Gus Dur. It also maps the peculiarities of the two figures' thoughts in applying humanism philosophy to education. This study employs a qualitative method by conducting library research. The study's findings indicate that Paulo Freire and Gus Dur's ideas incorporate humanistic educational qualities. Both are humanist intellectuals who strive to improve human dignity through education. The distinction is in the background. Freire has a foundation in traditional Western schooling. KH. Abdurrahman Wahid, on the other hand, represents a Muslim intellectual. Paulo Freire's concept of education that liberates is focused on humanity. Meanwhile, Gus Dur saw that anyone could have liberty if his every move was based on God. Freire's method is problem-solving education and critical thinking. Similar to Gus Dur, who glorified critical thinking in students. Future scholars should expand on the ideas of the two figures by employing a multi- and interdisciplinary method and type of research.